Emerging trends in lifecycle assessment of building construction for greenhouse gas control: implications for capacity building - Ruoxing Cao; Yu Hao; Yuanzhe Li; Wenrui Liao (Discover Applied Sciences)
Abstract This mini-review addresses the critical problem of significant greenhouse gas (GHG) emissions from the global construction industry, which accounts for 37% of energy-related carbon emissions. With global building areas expected to double by 2060, this paper aims to analyze carbon emission characteristics and control strategies throughout the buildings' entire life cycle, emphasizing the urgent need for effective life cycle carbon management. We introduce and contextualize life cycle assessment (LCA) methods, focusing particularly on Scope 1, 2, and 3 emissions across different life cycle stages of buildings—from design through demolition. Our key findings highlight the potential of intelligent grid energy management systems (EMS) to optimize carbon efficiency in real-time, a pioneering approach that has yet to be widely implemented. The review synthesizes global advancements in green building practices, particularly in regions like Europe, America, and China, and discusses the varied success of these regions in integrating comprehensive carbon management strategies throughout the building life cycle. We conclude with strategic recommendations for future research directions, policy-making, and international cooperation to enhance the sustainability of the construction industry. This study ultimately aims to contribute robust evidence supporting the adoption of advanced LCA methodologies and intelligent EMS in reducing the construction sector's carbon footprint. Graphical Abstract